Subclinical Hypothyroidism: A Review on Clinical Consequences and Management Strategies (Journal of Medicine, 2017)
Subclinical hypothyroidism (SCH) is defined as an elevated serum thyroid-stimulating hormone (TSH) level with normal free thyroid hormone values. The prevalence of subclinical hypothyroidism is 3 to 8 percent in the general population, and up to 15 to 18 percent in women who are older than 60 years. It is more common in women than men, and its prevalence increases with age. Of patients with SCH, 80% have a serum TSH of less than 10 mIU/L. Management strategies including screening and treatment of subclinical hypothyroidism are still controversial. The strongest arguments for levothyroxine therapy are the high risk of progression to overt hypothyroidism. Initiating levothyroxine replacement therapy is recommended for all patients with a TSH greater than 10 mIU/L, even if the free thyroxine concentration is within normal laboratory range. However, treatment of patients with a serum TSH level between 5 and 10 mIU/L remains controversial. There was insufficient evidence for a clinically significant relationship between subclinical hypothyroidism and adverse cardiac events or cardiac dysfunction. Conflicting results have been found on the association between subclinical hypothyroidism and cognitive impairment, depression and the risk of fractures. This narrative review aims to assess current evidence on the clinical aspects, as well as screening and treatment recommendations in adults with subclinical hypothyroidism.J MEDICINE January 2017; 18 (1) : 30-36